Des femmes au service de l’Évangile selon le livre des Actes: La collaboration de Priscilla à la mission paulinienne et à l’édification des communautés chrétiennes - Siffer, Nathalie (Judaïsme ancien, 2023)
In the Book of Acts, the question of the role and responsibility of women in the first Christian communities arises particularly in the case of Priscilla, the married woman featured in Acts 18, who is also mentioned several times in the Pauline corpus. Although her activity is always reported within the couple she forms with Aquilas, the fact remains that she is an eminent figure in the early Church. Indeed, not only did she appear to be a woman committed to spreading the Gospel, carrying out multiple tasks at the same time, but she also played a leading role in building up the communities. In order to understand the originality of her profile, we need to take a closer look at the data that testify to this singularity: her precedence in the couple’s relationship, her leadership within the nascent Christian movement, her role as a teacher-theologian, and overall, the importance of her missionary activity, which makes her one of Paul’s most valuable collaborators. In the dynamics of the first Christian mission, she is in many ways a key figure and an exceptional woman.